2022
DOI: 10.1007/s11033-022-08138-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel PIEZO1::CBFA2T3 and INO80C::SETBP1 fusion genes in an acute myeloid leukemia patient by RNA-seq

Abstract: Fusion genes are recurrent molecular aberrations in acute myeloid leukemia, with signi cant diagnostic and therapeutic value. The identi cation of novel fusion genes provides advanced biomarkers for diagnosis and facilitates the discovery of drug targets. Here we report a male AML patient with presence of PIEZO1::CBFA2T3 and INO80C::SETBP1 fusion genes detected by RNA sequencing. As far as we know, it is the rst time PIEZO1::CBFA2T3 and INO80C::SETBP1 are identi ed in AML patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…The vast majority of fusions identified in MPS studies are non-recurring, and, as such, have been identified as stochastic events [19]. While large-scale MPS efforts have been enormously productive in identifying fusion break points, novel oncofusions and their acting mechanisms are still being identified from MPS data at an accelerating pace [85][86][87][88][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], and while multiple fusion databases are available [64,121,122], a centralized and standardized hub akin to, for example, IntAct [123] for interaction data or UniProt [124] for protein information has yet to emerge.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%
“…The vast majority of fusions identified in MPS studies are non-recurring, and, as such, have been identified as stochastic events [19]. While large-scale MPS efforts have been enormously productive in identifying fusion break points, novel oncofusions and their acting mechanisms are still being identified from MPS data at an accelerating pace [85][86][87][88][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], and while multiple fusion databases are available [64,121,122], a centralized and standardized hub akin to, for example, IntAct [123] for interaction data or UniProt [124] for protein information has yet to emerge.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%